Targeting adipocyte differentiation with CRT0066101: activation of AMPK signaling in 3T3-L1 cells - Luo, Jinque; Wang, Ling; Zhang, Li; Tang, Wenyu; Deng, Meijing; Shi, Yuxin; Xu, Kun; Wu, Qingjun; Zhao, Jieyang; Zhang, Jinghuan; Li, Xin (Frontiers in Pharmacology, 2025)
IntroductionObesity is characterized by excessive fat accumulation resulting from adipocyte hypertrophy and hyperplasia, with adipocyte differentiation being a central process driving these changes.MethodsThe anti-adipogenic effects of CRT0066101 (CRT), a pan-protein kinase D (PKD) inhibitor, were evaluated in 3T3-L1 adipocytes. Potential drug targets of CRT were predicted using network pharmacology analysis. The expression of adipocyte-specific genes and proteins was assessed by western blotting and qRT-PCR. To examine the involvement of the AMPK pathway, cells were co-treated with CRT and the AMPK inhibitor Compound C.ResultsCRT significantly inhibited early-stage adipocyte differentiation, reduced lipid accumulation, and downregulated key adipogenic transcription factors, including PPARγ and C/EBPα. Mechanistically, CRT activated the AMPK pathway, a known negative regulator of adipocyte differentiation. Network pharmacology analysis further supported the involvement of AMPK in CRT’s anti-adipogenic action.DiscussionThese findings identify CRT as a novel modulator of adipocyte differentiation through AMPK activation and highlight its potential as a therapeutic candidate for obesity and metabolic syndrome.